Solubility and pH Value of 2 Different Root Canal Sealers: A Comparative Study - Showg Salem; Agila, Nora (Khalij-Libya Journal of Dental and Medical Research, 2024)
Background and objectives. The purpose of this study was to evaluate solubility and pH value of MTA-Fillapex compared to AH plus sealer. Methods. Forty sealer discs were prepared and incubated until complete setting of the sealers. The discs were divided into two equal main groups according to the tested material; Group I: 20 discs from MTA-Fillapex. Group II: 20 discs from AH Plus. Each group was further subdivided into 2 subgroups according to the evaluation test as follows; Subgroup A: used to evaluate the solubility of the sealer (10 disc). Subgroup B: used to evaluate pH of the sealer (10 disc). For solubility test, the discs were weighed using a precision balance to 0.0001 g. Then they were immersed in HBSS and left for 24 hours in incubator at 37°C, 95% relative humidity. The discs were removed from the containers and dried, reweighed. Solubility was calculated as percentage of mass loss. For pH test, the pH value was measured by a digital pH meter after (3, 24, 48, and 168 hours) from manipulation. Results were tabulated and statistically analyzed using a one-way ANOVA test followed by Pair-wise Newman keuls multiple comparison tests. Results. The result indicated that MTA-Fillapex showed mean percentage weight loss statistically significantly higher than AH Plus. MTA-Fillapex has shown an alkaline pH at all observation periods which was statistically significantly higher than AH Plus (p<.05). Conclusion. The current study concluded that the both sealers have solubility and pH in agreement with ISO 6876/2001 and ANSI/ADA specification no. 57. تم تحضير أربعين قرص مانع للتسرب وتحضينها حتى تمام تماسك المادة المانعة للتسرب. تم تقسيم الأقراص إلى مجموعتين رئيسيتين متساويتين حسب المادة المختبرة؛ المجموعة الأولى: 20 قرصًا من MTA-Filapex. المجموعة الثانية: 20 قرص من شركة AH Plus. تم تقسيم كل مجموعة إلى مجموعتين فرعيتين وفقًا لاختبار التقييم على النحو التالي؛ المجموعة الفرعية أ: تستخدم لتقييم ذوبان المادة العازلة (10 أقراص). المجموعة الفرعية ب: تستخدم لتقييم الرقم الهيدروجيني للمادة العازلة (10 أقراص). لاختبار الذوبان، تم وزن الأقراص باستخدام ميزان دقيق يصل إلى 0.0001 جم. ثم تم غمرهم في HBSS وتركوا لمدة 24 ساعة في الحاضنة عند درجة حرارة 37 درجة مئوية، ورطوبة نسبية 95٪. تمت إزالة الأقراص من الحاويات وتجفيفها وإعادة وزنها. تم حساب الذوبان كنسبة مئوية من فقدان الكتلة. بالنسبة لاختبار الرقم الهيدروجيني، تم قياس قيمة الرقم الهيدروجيني بواسطة مقياس الرقم الهيدروجيني الرقمي بعد (3، 24، 48، و 168 ساعة) من المعالجة. تم جدولة النتائج وتحليلها إحصائيا باستخدام اختبار ANOVA أحادي الاتجاه متبوعًا باختبارات المقارنة المتعددة لنيومان كيول. النتائج. أشارت النتيجة إلى أن MTA-Filapex أظهر متوسط نسبة فقدان الوزن أعلى بشكل ملحوظ إحصائيًا من AH Plus. أظهرت MTA-Fillapex درجة حموضة قلوية في جميع فترات المراقبة والتي كانت أعلى بشكل ملحوظ إحصائيًا من AH Plus (p<.05). الخاتمة. خلصت الدراسة الحالية إلى أن كلا المادتين العازلتين لهما قابلية ذوبان ودرجة حموضة متوافقة مع المواصفة ISO 6876/2001 ومواصفات ANSI/ADA رقم. 57.